2023
DOI: 10.1108/jpcc-03-2023-0016
|View full text |Cite
|
Sign up to set email alerts
|

Using multilevel mentoring as a situated learning approach to enhance the professional development of teachers in higher education

Yaw Owusu-Agyeman

Abstract: PurposeScholarly studies on mentoring have mostly focused on traditional mentor–mentee relationships, with little or no emphasis on how institutionalized mentoring activities that include different pedagogical approaches could be used to enhance the professional development of academics. To address this knowledge gap, this article examines how an institutionalized multilevel mentoring program could be used to enhance the professional development of early-career academics and academics in designated groups in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…O'Brien (2023) and Mittal & Upamannyu (2017) observed that mentoring in universities enhances job satisfaction, reduces turnover, and improves teaching and research outcomes. Furthermore, mentoring has been found to be instrumental in improving the quality of academic leadership and excellence in African universities (Ezimma et al, 2021;Owusu-Agyeman, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…O'Brien (2023) and Mittal & Upamannyu (2017) observed that mentoring in universities enhances job satisfaction, reduces turnover, and improves teaching and research outcomes. Furthermore, mentoring has been found to be instrumental in improving the quality of academic leadership and excellence in African universities (Ezimma et al, 2021;Owusu-Agyeman, 2024).…”
Section: Introductionmentioning
confidence: 99%